2014
DOI: 10.1007/s12035-014-9032-y
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 Regulates Axonal Outgrowth and Maturation of Primary Hippocampal Neurons

Abstract: Transient receptor potential melastatin 7 (TRPM7) is a calcium-permeable divalent cation channel and mediates neuronal cell death under ischemic stresses. In this study, we investigated the contribution of TRPM7 to neuronal development in mouse primary hippocampal neurons. We demonstrated that TRPM7 channels are highly expressed in the tips of the growth cone. Either knockdown of TRPM7 with target-specific shRNA or blocking channel conductance by a specific blocker waixenicin A enhanced axonal outgrowth in cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…TRPM7 is known to inactivate LIMK1 which in turn is a suppressor of cofilin (Arber et al, 1998; Meng et al, 2003; Meng et al, 2002). Recently, inhibition and knockdown of TRPM7 was shown to increase the rate of progression through neuronal development stages and increase the length of axons (Turlova et al, 2016). Some of TPRM7’s effects could be through phosphorylation of Tmods, which are present in axonal shafts (Fath et al, 2011).…”
Section: Tropomodulins and Tropomyosins – Discovery Structure And Rmentioning
confidence: 99%
“…TRPM7 is known to inactivate LIMK1 which in turn is a suppressor of cofilin (Arber et al, 1998; Meng et al, 2003; Meng et al, 2002). Recently, inhibition and knockdown of TRPM7 was shown to increase the rate of progression through neuronal development stages and increase the length of axons (Turlova et al, 2016). Some of TPRM7’s effects could be through phosphorylation of Tmods, which are present in axonal shafts (Fath et al, 2011).…”
Section: Tropomodulins and Tropomyosins – Discovery Structure And Rmentioning
confidence: 99%
“…Primary cortical cultures were prepared from E16 CD1 mice as previously described (24). Cells were plated on poly-D-lysine coated plates using Neurobasal culture medium at the desired density (1 3 10 5 per well) and maintained at 37°C in a humidified 5% CO 2 atmosphere.…”
Section: Primary Cortical Culturementioning
confidence: 99%
“…The importance of neurite outgrowth during brain development cannot be overstated as disruptions to this process have been associated to Down syndrome (Becker et al, 1986) and Fragile X Syndrome (Dierssen and Ramakers, 2006). Interestingly, a recent study by Turlova et al, 2016 reported that TRPM7 negatively regulates neurite outgrowth in cultured hippocampal neurons. They demonstrated that neurite length was increased after performing targeted knockdown of TRPM7 with shRNA.…”
Section: Discussionmentioning
confidence: 99%